"Don't Know What You Got till It's Gone": The Community Reinvestment Act in a Changing Financial Landscape. Issue 1 (2nd January 2021) - Ding, Lei; Nakamura, Leonard
Abstract: This study provides new evidence on the impact of the Community Reinvestment Act (CRA) on mortgage lending by taking advantage of an exogenous policy shock in 2014, which caused significant changes in neighborhoods' CRA eligibility in the Philadelphia market. The loss of CRA coverage leads to an over 10% decrease in purchase originations by CRA-regulated lenders. While nondepository institutions replace approximately half, but not all, of the decreased lending, their increased market share is accompanied by a greater involvement in riskier and more costly FHA lending. This study demonstrates how different lenders respond to the incentive of CRA credit.